(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, the distribution of poplar blister beetles, which cause serious damage to poplars in the conditions of Eastern Fergana, their larvae and their wintering, the development periods of male (♂) and female (♀) first-second generations, and the characteristics of the same insect’s infection with Aphytis proclia stated.